(3GdeDSSGJ GdeGdjI GdeMdjI h GdOhdjIs - (3TbjQj fhQj(B, (3ehSis; (3eMehO GHQGgje(B, (3fhQ hBNQhfs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2009)
(3CgejI GdfXGe GdeGdj hOhQ eDSSGJg(B- (3GdHfhc GdeQcRjI(B- (3GdHfhc GdJLGQjI(B- (3GdHfhc GdeJNUUI(B- (3Hfc GdEfeGA GdUfGYj(B- (3Hfc GdESJKeGQ(B- (3eDSSGJ hTQcGJ GdJCejf(B- (3eDSSI GdVeGf GdELJeGYj(B- (3UfGOjb GdJbGYO hGdEONGQ GdhXjaj(B- (3UfGOjb GdJhajQ GdHQjOj hGdEONGQj(B- (3UfGOjb GdESJKeGQ(B- (3GdeDSSGJ GdeGdjI GdOhdjI(B- (3GdTQcGJ GdeGdjI GdJYOOI GdLfSjGJ(B- (3GdHfc GdOhdjs
(3GdeQGLY U(B.397(3; GdedGMb U(B.355s
Keywords: (3GdCShGb GdeGdjIs; (3GdHfhc GdeQcRjIs; (3GdJMdjd GdeGdjs; (3GdeDSSGJ GdeGdjIs